Analysis on Shariah governance in Islamic banking: a comparative perspective - Hasan, Aznan; Md. Sawari, Mohd. Fuad (2011)
Shariah governance is the essence for a comprehensive regulatory and supervisory infrastructure of Islamic Banking and Finance system. It is the vehicles of the Islamic banking and financial regulatory and supervisory infrastructure. The overall compliance of Islamic banking and financial business is solely depending on the adequacy and efficiency of the Shariah governance. Ignoring or neglecting Shariah governance means creating a vacuum, and thus resulting to undermining the integrity of the Islamic financial system. Although the framework for Shariah Governance varies from one jurisdiction to another, generally the Shariah governance would comprise of two vital components vis-a-vis the Shariah advisory body appointed by regulators and the Shariah body set up by a financial institution in the Islamic banking and finance industry. This research aims to provide a comparative analysis and review of Shariah governance structures practices in different countries. The outcome of the research will contribute to the development of Islamic banking and financial institutions across the jurisdictions specifically in the regulatory framework governing practices on Shariah governance including the structures of Shariah Advisory Boards, their functions, rights and responsibilities. Apart from that, this research also aims to improve the current practices of Shariah governance in Islamic banking and finance industry.